Exploring Teriary Students’ Experience of Informal Digital Learning of English for Boosting English Receptive Skills - Maulida, Fariha Nur; Mardiana, Wiwik; Irfan, Syihabul (Indonesian Journal of English Language Studies (IJELS), 2022)
The speed of technology development facilities students in learning English digitally. They could express and use English in informal digital environment through social media and learning English application or resources. Informal Digital Learning of English (IDLE) contributes to students language enhancement. This study is want to dig in about the use of digital learning to informal and independent learning of English. Therefore, this research aims to explore how IDLE activity can engage receptive skills in university students and to explore how IDLE receptive skill activity can develop university students’ receptive skills. This study found that each individul can experience an increase in English receptive skills by going through the stages of learning using social media and English learning applications. IDLE-based learning can be built through the initiative and willingness of each individual, because this learning is not tied to a specific schedule or material to be studied. Each individual can organize and determine how they learn according to their wishes.